Ectopic lymphoid neogenesis in psoriatic arthritis. Issue 6 (12th January 2007) - Cañete, Juan D; Santiago, Begoña; Cantaert, Tineke; Sanmartí, Raimon; Palacin, Antonio; Celis, Raquel; Graell, Eduard; Gil-Torregrosa, Beatriz; Baeten, Dominique; Pablos, José L
Abstract : Background: Ectopic lymphoid neogenesis (LN) occurs in rheumatoid synovium, where it is thought to drive local antigen-dependent B cell development and autoantibody production. This process involves the expression of specific homing chemokines and the development of high endothelial venules (HEV). Objective: To investigate whether these mechanisms occur in psoriatic arthritis (PsA) synovium, where autoantibodies have not been described and the organisation and function of B cells is not clear, and to analyse their clinical correlates. Methods: Arthroscopic synovial biopsy specimens from patients with PsA before and after tumour necrosis factor α blockade were characterised by immunohistochemical analysis for T/B cell segregation, peripheral lymph node addressin (PNAd)-positive HEV, and the expression of CXCL13, CCL21 and CXCL12 chemokines in relation to the size of lymphoid aggregates. Results: Lymphoid aggregates of variable sizes were observed in 25 of 27 PsA synovial tissues. T/B cell segregation was often observed, and was correlated with the size of lymphoid aggregates. A close relationship between the presence of large and highly organised aggregates, the development of PNAd+ HEV, and the expression of CXCL13 and CCL21 was found. Large organised aggregates with all LN features were found in 13 of 27 tissues. LN in PsA synovitis was not related to the duration, pattern or severity of the disease. The synovial LN pattern remained stable over time in persistent synovitis, but a complete response to treatment was associated with a regression of the LN features. Conclusions: LN occurs frequently in inflamed PsA synovial tissues. Highly organised follicles display the characteristic features of PNAd+ HEV and CXCL13 and CCL21 expression, demonstrating that the microanatomical bases for germinal centre formation are present in PsA. The regression of LN on effective treatment indicates that the pathogenic and clinical relevance of these structures in PsA merits further investigation.